The effect of stressors and resilience factors on mental health of recent refugees in Austria - Sebastian Leitner; Michael Landesmann; Judith Kohlenberger; Isabella Buber-Ennser; Bernhard Rengs (The Vienna Institute for International Economic Studies (wiiw), 2019)
Given the exposure to stressors in their home countries, during their migration and in the phase after arrival, refugees are particularly vulnerable to mental health problems. At the same time, their access to adequate healthcare and other social infrastructure might be hampered by factors such as lack of knowledge as well as cultural and language barriers. In addition to other factors, this reduces their ability to take part in social activities as well as their integration into the labour market of the host societies. We examine the prevalence of mental disorders in the refugee population from Afghanistan, Iraq and Syria who arrived in Austria recently, drawing on data from a refugee survey conducted between December 2017 and April 2018 in Austria with a specific focus on Vienna, Salzburg, Graz, Linz and Innsbruck (FIMAS+INTEGRATION). We found a high share of refugees (32%) to have moderate or severe mental health problems. In particular, young refugees (15-34 years) show higher risk levels. When investigating the effects of stressors on the mental health situation, we found a positive association with e.g. experienced discrimination in Austria and the fear for partners and children left behind. In contrast, the results show a negative correlation for a couple of mitigating factors that foster resilience, i.e. proficiency in the German language, being employed (including volunteer work), having more supportive relationships and satisfaction with the housing situation.
Keywords: I10; J15; F22; 330; refugees; mental health; social integration; labour market integration